Thermal Environment Analysis And HVAC ( Heating, Ventilating, Air Conditioning) Installation Basen On CFD (Computational Fluid Dynamics) At PTPN III PKS Rambutan Work Station - Khairul Imam (Journal Basic Science and Technology, 2021)
This research was conducted based on observations at the PTPN III work station, the operator who did not feel comfortable with the thermal environment was the operator of the sterilizer station. The sterilizer station has heat radiation from the sterilizer machine, heat radiation of machine support equipment and heat conduction of the station roof. All the heat radiation affects the station air temperature. Based on data collection, the average air temperature at the station is 34.59 oC. The operator's reaction to this heat exposure is to take breaks during working hours and when operating machinery. Overall, the proportion of work of machine operators and track control operators who are at the sterilizer station is small. The method used to analyze the impact of heat exposure is the calculation of the Heat Stress Index (HSI) and the proposed repair of HVAC (Heating, Ventilating, Air Conditioning) installations simulated with CFD (Computational Fluid Dynamics). Based on the analysis of the processed data, the average HSI of operators at the sterilizer stations in 13 work areas is 83.62%, which indicates that all operators are exposed to heat. There is a fairly strong positive correlation between HSI and the operator's physiological response of R2 = 0.303. This indicates that the HSI felt by the operator can increase the physiological response in the form of an increase in the number of metabolic activities. There is a very strong negative correlation between the Heat Stress Index value and the total proportion of work operators of R2 = 0.914. This indicates that the increase in HSI makes the operator work proportion decrease. Improvements made were the installation of Air Conditioning in the form of the installation of the L-90 Turbine Ventilator. Based on the simulation, it is known that this improvement will reduce the perception of heat for the operator and reduce the level of operator discomfort.